A Correlational Investigation on Impact of Narcissism and Implication of Job Satisfaction on Nigerian Government Employees: A Study of Yobe State (Global Journal of Management and Business Research, 2019)
There is a dearth of narcissism and job satisfaction related studies in North East Nigerian context and to understand these two constructs, their correlation and effect on each other present investigation was carried out. Additionally, it was tried to find out the influence of different important independent variables like income, age and work experience on the personality type narcissism and the work attitude job satisfaction. The research also endeavoured to categorize and rank the assortment of job satisfaction factors for the107 government employees surveyed. The data was collected through Narcissistic Personality Inventory (NPI) and Job Satisfaction Scale and to reach the outcomes various statistical tools like Cronbach's Alpha, Pearson Correlations (bivariate), Means, Standard Deviation and Percentages were employed. Having realized the reliability of the instruments to be as per set benchmarks and testing the stated hypotheses it was found that money was not necessarily important factor of job satisfaction. Further narcissism and job satisfaction were not related and other variables as already mentioned came up with notable findings which prompted many managerial recommendations and stimuluses for future researches.
Keywords: correlational study; narcissism; job satisfaction; government employees; yobe state; nigeria